Blocking of radiative thermal conduction in Zn2+-Incorporated high-entropy A2B2O7 fluorite oxides. Issue 23 (1st December 2021) - Song, Dowon; Ryu, Myeungwoo; Kwon, Jiseok; Lyu, Guanlin; Kim, Junseong; Jeon, Hak-Beom; Song, Taeseup; Paik, Ungyu; Yang, Byung-il; Jung, Yeon-Gil; Oh, Yoon-Suk
Abstract: In this study, a high-entropy approach was employed to design a new single-phase A2 B2 O7 oxide for thermal insulation applications. Multicomponent high-entropy oxides, containing up to seven different cations, were successfully synthesized in a single defective fluorite structure. We observed that the incorporation of the functional cation, Zn 2+, effectively blocked the heat radiation phenomenon by reducing the photon mean free path, and further reduced the high-temperature thermal conductivity owing to the larger free carrier concentration originated from the large number of oxygen vacancies. Although a large concentration of Zn 2+ caused a slight reduction in thermal expansion, this study suggests that functional cations can be easily incorporated; thus, expanding the material diversity beyond the typical doping levels to develop new thermal barrier materials.